Performance analysis of yellow hydrogen production in the UAE - Ahmed Al Makky; Hasan A. Kanjo; Tareq Salameh; Abdul-Kadir Hamid; Mousa Hussein (Energy Conversion and Management: X)
This study offers a novel techno-economic evaluation of a small hydrogen generation system included into a residential villa in Sharjah. The system is designed to utilize solar energy for hydrogen production using an electrolyzer. The study assesses two scenarios: one lacking a fuel cell and the other incorporating a fuel cell stack for backup power. The initial scenario employs a solar-powered electrolyzer for hydrogen production, attaining a competitive levelized cost of energy (LCOE) of $0.1846 per kWh and a hydrogen cost of $4.65 per kg. These data underscore the economic viability of utilizing electrolyzers for hydrogen generation. The system produces around 1230 kg of hydrogen per annum, rendering it appropriate for many uses. Nevertheless, the original investment expenditure of $73,980 necessitates more optimization. The second scenario includes a 10 kW fuel cell for energy autonomy. This scenario has a marginally reduced LCOE of 0.1811 $/kWh and a cumulative net present cost of $72,600. The fuel cell runs largely at night, proving the efficiency of the downsizing option in decreasing capital expense. The system generates electricity from solar panels (66.1 MWh/year) and the fuel cell (16.9 MWh/year), exhibiting a multi-source power generating technique. The results indicate that scaled-down hydrogen generation systems, both with and without fuel cells, may offer sustainable and possibly lucrative renewable energy options for household use, especially in areas with ample solar resources such as Sharjah.